Lung cancer and combined pulmonary fibrosis and emphysema with anti-ARS antibody - Tanimura Riho; Nishino Kengo; Iwade Ryosuke; Abe Ryo; Okauchi Shinichiro; Sasatani Yuika; Satoh Hiroaki (Sciendo, 2022)
A 59-year-old man who had smoked for 23 pack-years was admitted to our hospital because of two-month history of back pain. The chest computed tomography scan demonstrated combined pulmonary fibrosis and emphysema (CPFE) and an irregular shaped nodule in the left lower lobe of the lung. A biopsy obtained from samples from subcarinal lymph nodes revealed non-small cell lung cancer. Anti-aminoacyl-tRNA synthetase (ARS) antibody was elevated up to 166 U/mL, although he had no symptoms suggestive connective tissue diseases. It is well known that most of CPFE patients are current or former heavy smokers, and some researchers described the relationship between CPFE and connective tissue diseases. To our best knowledge, this was the first report of lung cancer in patient with anti-ARS antibody-positive CPFE. In some anti-ARS antibody-positive patients, smoking might have a relationship with development of CPFE and lung cancer.